Biodiversity conservation and poverty alleviation : exploring the evidence for a link - Roe, Dilys (Hoboken, NJ : Wiley-Blackwell, 2013)
Biodiversity conservation and poverty alleviation are both important societal goals demanding increasing international attention. While they may seem to be unrelated, the international policy frameworks that guide action to address them make an explicit assumption that conserving biodiversity will help to tackle global poverty. Part of the Conservation Science and Practice Series published with the Zoological Society of London, this book explores the validity of that assumption. The book addresses a number of critical questions: Which aspects of biodiversity are of value.
pt. 1. Biodiversity, ecosystem services and poverty : the potential for synergies -- pt. 2. Biodiversity and poverty relationships in different ecological settings -- pt. 3. Poverty impacts of different conservation interventions -- pt. 4. Distributional and institutional issues -- pt. 5. Biodiversity and poverty relationships in the context of global challenges.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Biodiversity conservation -- Economic aspects; Poverty -- Prevention -- Environmental aspects; Biodiversity conservation -- Economic aspects; Poverty -- Prevention -- Environmental aspects; NATURE -- Animals -- Wildlife; SCIENCE -- Life Sciences -- Biological Diversity; Electronic books; Electronic books; Electronic books